Beneficial Effects of Multi-Micronutrient Supplementation with Collagen Peptides on Global Wrinkles, Skin Elasticity and Appearance in Healthy Female Subjects - Rachael Gibson; Lieselotte Krug; David L. Ramsey; Azadeh Safaei; Sue Aspley (Adis, Springer Healthcare, 2024)
Abstract Introduction With ageing, collagen production slows down, leading to wrinkle appearance and loss of elasticity. Replenishing key structural molecules through oral supplementation is a promising strategy that complements the topical delivery of cosmetic products and creates a holistic skincare regimen. The present study assessed the effectiveness of a food supplement with collagen peptides, vitamins and minerals in improving the quality of the skin and general wellbeing of healthy women. Methods This was an open-label study of 135 women aged between 45 and 65 years. A 3-month treatment phase followed a 4-week washout phase, with visits scheduled at baseline and after each month of treatment. Subjects received three tablets of Richelet Skin Renewal daily. The primary outcome was change from baseline to month 3 in global wrinkles score by expert grader analysis. Secondary outcomes included changes in skin elasticity and other skin attributes, product assessment via self-perception questionnaires and total antioxidant status. Results A total of 116 subjects completed the study. The mean global wrinkles score indicated a statistically significant decrease from 5.9 at baseline to 5.0 at month 3 (p < 0.0001), with 83.6% of subjects showing an improvement; significant changes were reported at all intermediate visits. The increase in skin elasticity was also statistically significant (R2 score 0.74 at month 3; p < 0.0001). All subjects (100%) demonstrated significant improvements in skin texture, skin tone evenness, skin radiance and overall skin quality at the month 3 visit. Conclusions The study product achieved statistically significant, noticeable effects on global wrinkles, skin elasticity and a range of skin attributes after 3 months of use in healthy women. These results strengthen the evidence for supplementation of collagen peptides and other micronutrients as an effective component of anti-ageing skincare.